Running away from stress: How regulatory modes prospectively affect athletes' stress through passion. Issue 6 (9th June 2015) - Lucidi, F.; Pica, G.; Mallia, L.; Castrucci, E.; Manganelli, S.; Bélanger, J. J.; Pierro, A.
Abstract : A prospective field study conducted with runners training for an upcoming marathon (Marathon of Rome 2013) examined the relation between regulatory modes, locomotion and assessment, and stress. Integrating regulatory mode theory and the dualistic model of passion, we hypothesized that the relation between regulatory modes (evaluated 3 months before the race) and the experience of stress approaching the marathon, is mediated by the type of passion (harmonious vs obsessive) athletes experience with regard to marathoning. Results revealed that (a) locomotion positively predicted harmonious passion, which in turn reduced athletes' experience of stress; and (b) assessment positively predicted obsessive passion, which in turn enhanced athletes' experience of stress. Overall, the present results suggest that proximal psychological mechanisms such as basic regulatory mode orientations can predict distal outcomes such as stress indirectly through their relation with motivational phenomena such as passion.